Disbudding pain in calves: mitigating short-term effects and exploring long-term consequences - Santos, Zimbábwe Osório (2023)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Ciências Agrárias, Programa de Pós-Graduação em Agroecossistemas, Florianópolis, 2023.